Influence of technological procedures on viability, probiotic and anti-mycotoxin properties of Saccharomyces boulardii RC009, and biological safety studies - Poloni, Valeria Lorena (2021)
The objective was to evaluate the technological processing (protection strategies and storage conditions) influence on viability, on probiotic properties and adsorbent aflatoxin B1 capacity of S. boulardii RC009. Also, the yeast biological safety was evaluated. Lyophilisation (DL) and encapsulation ​+ ​lyophilisation (EL) were conducted. Yeast protected with maltodextrin (M) or WPC stored at 4 ​°C reduced 1 and 2 log the viability, respectively. Yeast protected with M stored at 25 ​°C reduced 1 log after 70 ​d; with WPC the viability significantly reduced 3 log after 30 ​d. Technological processing improved the coaggregation's capacity with pathogens and DL process allowed the greatest AFB1 adsorption. S. boulardii 106 ​cells/mL were no toxic to Vero cells (p˂0.05). Saccharomyces boulardii RC009 protected with M or WPC maintained viability after technological processing. It possesses a great capacity for AFB1 adsorption and probiotic properties and could be considered a candidate with proven safety for functional food products development.